Effects of Fe Dosage in Newborn Pigs on Preweaning and Subsequent Nursery Performance - H. Williams; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; R. D. Goodband; A. Holtcamp (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 336 newborn pigs (DNA 241 × 600, initially 3.83 ± 0.114 lb BW) were used in a 63-d study evaluating the effects of increasing injectable Fe dose on preweaning and subsequent nursery pig performance and blood Fe status. GleptoForte (Ceva Animal Health, LLC, Lenexa, KS) contains gleptoferron which is an Fe macro-molecule complex that is used as an injectable Fe source for preweaned piglets. A total of 28 litters were used and on the day of processing (approximately d 3 after birth) all piglets were weighed and six barrows and six gilts per litter were allotted to 1 of 6 treatments in a completely randomized design. Treatments consisted of a negative control receiving no Fe injection and increasing injectable Fe to achieve either 50, 100, 150, 200 mg; or 200 mg plus a 100-mg injection on d 11 post-farrowing. Piglets were weighed and blood samples were taken on d 3, 11, and 21 of age to determine blood Fe status and growth performance. Then pigs were weaned at approximately 21 d of age and allotted to nursery pens based on body weight (BW) and corresponding treatment in a completely randomized design with 5 or 6 pigs per pen and 10 pens per treatment. Common diets were fed throughout the nursery in 3 phases. Blood samples were taken on d 21 (weaning), 35, and 63 to determine blood Fe status. During the preweaning phase, increasing injectable Fe up to 100 mg improved (quadratic;P<0.05) average daily gain (ADG) and d 21 BW with no further improvement thereafter. There was no evidence of differences (P>0.10) between the 200 mg and 200 mg + 100 mg treatments for growth. For the nursery period, increasing Fe dosage improved (linear;P<0.05) ADG, average daily feed intake (ADFI), and d 63 BW. Also, increasing injectable Fe up to 150 mg improved (quadratic;P= 0.007) feed efficiency (F/G) with no further improvement with increased dosage. There was no evidence of differences (P>0.05) between the 200 mg and 200 mg + 100 mg treatments for growth. Significant treatment × day interactions (P= 0.001) were observed for hemoglobin (Hgb) and hematocrit (Hct). The interactions occurred because pigs that had less than 150 mg of injectable Fe had decreased values to d 21 and then increased to d 63 while pigs with 150 or 200-mg of injectable Fe had increased values to d 21 then stayed relatively constant to d 63. In summary, preweaning and nursery growth performance and blood Fe status were maximized with a 200 mg Fe injection at processing. Providing an additional 100 mg of Fe on d 11 of age increased Hgb, Hct, and serum Fe values at weaning and 14 d into the nursery but did not provide a growth performance benefit in farrowing or nursery.
Keywords: Fe; gleptoferron; growth performance; nursery